Aptamer/magnetic-MIP dual-recognition sandwich biosensor for rapid and recyclable determination of kanamycin in food - Tingting Wang; Fengjuan Zhao; Zhiguang Suo; Yong Liu; Yawei Huang; Min Wei (Analytica Chimica Acta, 2026)

Structural changes of costameres and actomyosin induced by postmortem resonant stimulation - Wanhong He; Yingbo Peng; Haixia Huang; Hao Wen; Chuanfeng Liu; Zhenzhen Li; Yawei Zhang (Food Research International, 2026)

Decoding flood hazard responses to reticular river network changes using interpretable machine learning - Shanheng Huang; Peng Wang; Zulin Hua; Yueyang Dong; Rongxu Chen; Yawei Hu; Shimin Tian (Journal of Hydrology, 2026)

Light-triggered molecular lever in a MOF@COF nanosheet for synergistic enhancement of heat and mass transfer in CO2 photothermal desorption - Jingyu Bao; Mingjie Zhou; Zuxue Bai; Yawei Xie; Xuehui Jia; Jiajun Zeng; Yujie Huang; Ruimeng Wang; Jianmin Chen; Zhaowei Jia; Liqin Zhou; Zhongxing Zhao; et al. (Chemical Engineering Journal, 2026)

The meteorological and anthropogenic drivers of O3 and PM2.5 pollution in China's Ningbo based on WRF-CMAQ-ISAM - YuZhan Xie; Tijian Wang; Pulong Chen; Kuanguang Zhu; Tao Niu; Rong Li; Mengmeng Li; Hao Wu; Yawei Qu; Xu Liu; Congwu Huang (Atmospheric Pollution Research, 2026)

A portable source-informed machine learning framework for predicting heavy metals in legacy smelting sites with strong spatial heterogeneity - Xu Cao; Yan Liang; Yawei Zhao; Tianhuan Chen; He Huang; Tian Xie (Journal of Hazardous Materials, 2026)

Cross-scale mechanisms and molecular–ecological thresholds of phthalate stress in the cucumber–soil system - Zhe Li; Lei Wang; DongDong Tuo; FuXin Huang; YaWei Shi; Ying Zhang (Journal of Hazardous Materials, 2026)

A computational screening study of Dual-Metal M1M2@1T-MoS2 with various coordination environments as catalysts for the hydrogen evolution reaction - Tingting Li; Guohao Yin; Haiyan Zhu; Shanlin Chen; Chou Wu; Shaobo Jia; Ghulam Meeladi; Yawei Li; Yixuan Huang (Fuel, 2026)

The Priming Impacts of Early Hypoxia Exposure in Abalone Parents Are Transmitted to Offspring - Yawei Shen; Yue Dai; Qizhen Xiao; Miaoqin Huang; Xuan Luo; Caihuan Ke; Weiwei You (Molecular Ecology, 2026)
The early environmental disturbances may have lasting effects on the sensitivity and acclimation abilities of organisms in later life stages or even in subsequent generations. However, measuring the responses of marine species with long generation times across multiple generations is challenging. Here, we investigated the inter‐generational carryover effects of early hypoxia exposure on Pacific abalone ( Haliotis discus hannai ), which takes two years to reach reproductive maturity. A five‐year study revealed that embryonic hypoxia exposure in abalone parents (F 0 ) has long‐lasting effects, which makes offspring (F 1 ) have higher specific growth rates and hypoxia tolerance despite these offspring having never been exposed to hypoxia. Embryonic hypoxia exposure did not reduce the genetic diversity ( Na , Ne , I , Ho , He and F ) of abalone between two generations, nor did it result in genetic differentiation ( F st and Nei's genetic distance) within a single generation. However, natural selection during the two‐year culture period may have favoured F 0 individuals with superior fitness traits to survive, ultimately driving genetic divergence among the F 1 generation. Furthermore, differentially expressed genes (e.g., mthfr and shmt1 ) that reflect the single‐generational, inter‐generational, and multi‐generational effects were involved in methylenetetrahydrofolate reductase activity and one carbon pool by folate. These genes might mediate the process by which F 0 embryonic hypoxia exposure alters the adaptive traits of the F 1 generation. This study revealed that the priming impacts of early hypoxia exposure might persist across generations through both genetic and non‐genetic mechanisms, providing insights for protecting marine organisms under global climate change.

Atmospheric reaction molecular network suggests transformation-driven chemodiversity of secondary organic aerosols - Feifei Li; Jitao Lv; Shanshan Tang; Qiurui Zhang; Yiru Qin; Qiying Nong; Xianwei Wang; Yongshun Huang; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2026)

Investigating the impact of different abuse methods on the thermal runaway behavior of lithium batteries under high-rate charge and discharge conditions - Yajun Huang; Weifeng Xu; Xiongqi Shen; Yinquan Zhao; Yang Cao; Wei Bai; Junling Wang; Yawei Lu; Zhirong Wang (Process Safety and Environmental Protection, 2026)

Integrating electronic sensory, untargeted metabolomics, and FT-NIR spectroscopy with machine learning for rapid origin discrimination and quality assessment of Chebulae Fructus - Yuhang Li; Wei He; Hanwen Zhang; Yue'e Li; Xiaomeng Li; Guokan Ge; Yawei Huang; De Ji (Food Research International, 2026)

Hysteretic behavior of reinforced ultra-high-performance concrete columns under combined axial and flexural loads - Qiwu Wang; Zhi Fang; Wenjie Zheng; Fei Peng; Yawei Fang; Jiaxing Chen; Hua Huang (Bulletin of Earthquake Engineering, 2026)

Invertible neural network for real-time inversion and uncertainty quantification of ultra-deep resistivity measurements - George Bittar; Sihong Wu; Yawei Su; Shubin Zeng; Jiajia Sun; Xuqing Wu; Yueqin Huang; Jiefu Chen (Computers & Geosciences, 2026)

Excellent infrared radiation performance and significant energy-saving efficiency of LaAlO3 ceramics via Ca2+/Co2+ co-doping - Qinghu Wang; Yangxi Liu; Guoping Wei; Liang Huang; Xueqing Wang; Shaobai Sang; Yibiao Xu; Xiong Liang; Yawei Li; Jiangtao Li; Olena Volkova; Emad M.M. Ewais; et al. (Chemical Engineering Journal, 2026)

Landslide assessment research in the three gorges reservoir area: A review of methodological advances and future directions - Yuandong Huang; Chong Xu; Xiaoyi Shao; Xiangli He; Zikang Xiao; Xiwei Xu; Yawei Xie; Xuning Nie; Xin Li (Bulletin of Engineering Geology and the Environment, 2026)

Lactobacillus rhamnosus GG-derived extracellular vesicles improve cholestatic liver injury by regulating the gut microbiota and bile acid metabolism - Zhongyu Wang; Yubo Wang; Yawei Qiu; Andrea Del Pilar Abreo Medina; Yongwang Liu; Mengdie Shi; Jinyan Li; Yanyan Wang; Xianjiao Liu; Xingxiang Chen; Kehe Huang; Yunhuan Liu (Chemical Engineering Journal, 2025)

A Y-shaped DNA-CRISPR-Cas12a Synergy fluorescent aptasensor for ultrasensitive detection of Aflatoxin B1 - Yawei Huang; Muyue Li; Zhuang Yang; Min Wei; Zhiguang Suo (Food Bioscience, 2025)

Study on the NO2 pollution and its connection with PM2.5 and O3 in Dazhou based on source apportionment - Xu Liu; Pulong Chen; Congwu Huang; Tijian Wang; Tao Niu; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu (Atmospheric Pollution Research, 2025)

Unraveling the health contributions of five key bioactives in virgin olive oil: A dose-based comparative review - Yunfei Huang; Wenqing He; Mengyao Zhao; David Julian McClements; Yawei Xu; Lu Li; Wanyi Dong; Xueqin Hu; Chunmei Li (Trends in Food Science & Technology, 2025)

The impact of the COVID-19 epidemic on anthropogenic emissions in the Beijing-Tianjin-Hebei region of China based on 3DVar sectoral emission inversion - Congwu Huang; Tao Niu; Tijian Wang; Mengmeng Li; Rong Li; Chaoqun Ma; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu; Yuzhan Xie (Journal of Hazardous Materials, 2025)

Excellent lithium storage performance of SnOx/Ti3C2 with low Sn content by controlling the oxygen vacancy content - Tingting Xu; Yawei Li; Jinghan Zhang; Haixiang Huang; Bogu Liu; Xiaohong Chen; Hong Zeng; Ying Wu (Chemical Engineering Journal, 2025)

The impact of indoor air quality on work performance in urban office spaces: A machine learning approach - Xinyi Huang; Xiaohong Zheng; Yawei Xu; Jiale Zhai; Dengyun Wang; Hua Qian (Building and Environment, 2025)

Investigation on the inhibition mechanism of thermal runaway propagation in high-rate cycling lithium-ion pouch cells - Yajun Huang; Xiongqi Shen; Yinquan Zhao; Junling Wang; Yang Cao; Wei Bai; Yu Fan; Yawei Lu; Zhirong Wang (Process Safety and Environmental Protection, 2025)

Mechanisms of antifungal activity of ehimensin F6 produced by Paenibacillus ehimensis HD against Penicillium expansum - Yuqing Huang; Dandan Liu; Yahui Liu; Ziwei Jia; Tengteng Zhao; Zhen Zhao; Yawei Ning; Xiaohui Liang; Zhixin Wang (International Journal of Food Microbiology, 2025)

Increased spike density and enhanced vegetative growth as primary contributors to improvement of dryland wheat yield via surface mulching - Yuwei Chai; Yawei Li; Rui Li; Lei Chang; Hongbo Cheng; Jiantao Ma; Yuqing Qin; Fanxiang Han; Changgang Yang; Yuzhang Chen; Qian Chen; Yao Zhang; et al. (Field Crops Research, 2025)

Modeling of non-grouted interlocking brick masonry using rigid-body-spring model - Yanan Lu; Lihua Huang; Xihong Zhang; Tingwei Shi; Yawei Zhu (Engineering Structures, 2025)

Proteomic insights from extracellular vesicles into the molecular mechanisms of health effects induced by Per- and polyfluoroalkyl substances - Yanping Li; Yadan Luo; Yang Liu; Na Li; Kai Huang; Lingxiangyu Li; Zhigang Li; Chao Han; Nali Zhu; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2025)

Revealing global supply risk of critical minerals essential for low-carbon energy technologies - Xinran Xing; Yawei Huang; Yao Wang; Heming Wang; Peng Wang; Tao Dai; Gang Liu; Asaf Tzachor (Journal of Cleaner Production, 2025)

Olanzapine exposure disordered lipid metabolism, gut microbiota and behavior in zebrafish (Danio rerio) - Yawei Wang; Fu You; Zhenyi Huang; Yuan Liu; Boya Yang; Xulu Chang; Guokun Yang; Xue Tian; Shikun Feng; Xiaolin Meng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Transcriptome analysis of hybrid abalone (Haliotis discus hannai ♀ × H. fulgens ♂) reveals non-additive effects contributing to growth heterosis at early summer water temperature in Fujian - Zekun Huang; Yawei Shen; Xingze Wang; Qizhen Xiao; Yi Wang; Yang Gan; Zhaofang Han; Wanbo Li; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2025)

Assessing the environmental impacts associated with China's battery minerals and technologies - Yawei Huang; Heming Wang; Asaf Tzachor (Resources, Conservation and Recycling, 2025)

3DVar sectoral emission inversion based on source apportionment and machine learning - Congwu Huang; Tao Niu; Tijian Wang; Chaoqun Ma; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu (Environmental Pollution, 2024)

Further geochronological constraints on the Xiuyan impact crater in northeast China - Zeyang Zhu; Chang Huang; Jing Wu; Yawei Li; Zhihao Sun; Min Zhang; Bin Zhang; Sheng-Hua Li; Jiaqi Liu (Frontiers of Earth Science, 2024)

Supplementation with Akkermansia muciniphila improved intestinal barrier and immunity in zebrafish (Danio rerio) - Yawei Wang; Zhenyi Huang; Zewei Gui; Boya Yang; Fu You; Guokun Yang; Xindang Zhang; Xulu Chang; Xiaolin Meng (Fish & Shellfish Immunology, 2024)

Carryover effects of embryonic hypoxia exposure on adult fitness of the Pacific abalone - Yue Dai; Yawei Shen; Caihuan Ke; Xuan Luo; Miaoqin Huang; Huoqing Huang; Weiwei You (Environmental Research, 2024)

A high throughput method to assess the hypoxia tolerance of abalone based on adhesion duration - Yue Dai; Yawei Shen; Yanbo Liu; Weiwei Xia; Jiawei Hong; Yang Gan; Jie Huang; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2024)

High throughput identification of carbonyl compounds in natural organic matter by directional derivatization combined with ultra-high resolution mass spectrometry - Shiyang Yu; Shanshan Tang; Jitao Lv; Feifei Li; Zichun Huang; Lixia Zhao; Dong Cao; Yawei Wang (Water Research, 2024)

Effects of Dietary Valine Chelated Zinc Supplementation on Growth Performance, Antioxidant Capacity, Immunity, and Intestine Health in Weaned Piglets - Tuan Zhang; Nan Zhang; Shuyu Peng; Yawei Zhang; Huakai Wang; Shiyu Huang; Min Zhu; Yongxi Ma (Biological Trace Element Research, 2024)
This study was conducted to investigate the effects of dietary valine chelated zinc (ZnVal) supplementation on growth performance, antioxidant capacity, immunity, and intestine health in weaned piglets. A total of 240 healthy 35-day-old weaned piglets (Duroc × Landrace × Yorkshire, average weight 10.70 ± 0.14 kg) were randomly divided into five groups with six replicate pens and eight piglets per pen. Dietary treatments were a corn–soybean meal basal diet supplemented with 0, 25, 50, 75, and 100 mg/kg ZnVal, respectively. The experiment lasted for 28 days. Results showed that average daily gain (ADG) was increased ( P < 0.05) by ZnVal with 75–100 mg/kg supplementation on days 15–28 and with 50–100 mg/kg supplementation on days 1–28. Supplementation of 25–100 mg/kg ZnVal reduced ( P < 0.01) the diarrhea rate of weaned piglets on days 1 to 14 and 1 to 28. Dietary supplementation with 25–100 mg/kg ZnVal increased ( P < 0.05) copper/zinc-superoxide dismutase (Cu/Zn-SOD) and decreased malonaldehyde (MDA) activities in the serum on day 14 and 28. Supplementation of 25–100 mg/kg ZnVal increased ( P < 0.05) glutathione peroxidase (GSH-Px) activity in serum on day 14. Additionally, the supplementation of 75 mg/kg ZnVal significantly increased the activity of superoxide dismutase (SOD) and Cu/Zn-SOD in the liver ( P < 0.05). Furthermore, the supplementation of 25–100 mg/kg ZnVal significantly increased the total antioxidant capacity (T-AOC) in the liver ( P < 0.05). Higher ( P < 0.05) concentrations of IgG in the serum were measured from piglets supplemented with 75–100 mg/kg ZnVal on day 14 and dietary supplementation with 25–100 mg/kg ZnVal increased the level of immunoglobulin G (IgG) in serum on day 28 ( P < 0.05). In addition, higher ( P < 0.05) concentrations of immunoglobulin A (IgA) in the duodenum and ileum were measured from piglets supplemented with 75 mg/kg ZnVal and the supplementation of 25–100 mg/kg ZnVal also showed a higher ( P < 0.05) concentration of immunoglobulin G (IgG) in duodenum. Supplementation of 50–100 mg/kg ZnVal increased the villus height and villus height/crypt depth of jejunum ( P < 0.05). Moreover, dietary supplementation with 75–100 mg/kg ZnVal showed a higher ( P < 0.05) concentration of zinc in the liver and supplementation of 50–100 mg/kg ZnVal increased ( P < 0.05) the concentration of zinc in the heart, spleen, and kidney. In conclusion, the present research showed that supplementation of ZnVal improves growth performance by increasing antioxidant capacity and immunity and regulating intestinal morphology and the optimal inclusion level of ZnVal was 65~80 mg/kg.

Facet-dependent transformation and toxicity of nanoscale zinc oxide in the synthetic saliva - Xiang Zhang; Yunpeng Huang; Jikun Wang; Jie Tang; Yang Mei; Nali Zhu; Zhigang Li; Lingxiangyu Li; Yawei Wang (Journal of Environmental Sciences, 2024)

Reducing oil absorption in pea starch through two-step annealing with varying temperatures - Shumin Xie; Zihan Li; Qingfei Duan; Weijuan Huang; Wei Huang; Yawei Deng; Pei Chen; Fengwei Xie (Food Hydrocolloids, 2024)

TREM2 Deficiency Aggravates NLRP3 Inflammasome Activation and Pyroptosis in MPTP-Induced Parkinson’s Disease Mice and LPS-Induced BV2 Cells - Peiting Huang; Zhanyu Zhang; Piao Zhang; Jiezhu Feng; Jianwei Xie; Yinjuan Zheng; Xiaomei Liang; Baoyu Zhu; Zhenzhen Chen; Shujun Feng; Lijuan Wang; Jiahong Lu; et al. (Molecular Neurobiology, 2024)
Microglia-mediated neuroinflammation plays a crucial role in the pathogenesis of Parkinson’s disease (PD). Triggering receptor expressed on myeloid cells 2 (TREM2) confers strong neuroprotective effects in PD by regulating the phenotype of microglia. Recent studies suggest that TREM2 regulates high glucose-induced microglial inflammation through the NLRP3 signaling pathway. This study aimed to investigate the effect of TREM2 on NLRP3 inflammasome activation and neuroinflammation in PD. Mice were injected with AAV-TREM2-shRNA into both sides of the substantia nigra using a stereotactic injection method, followed by intraperitoneal injection of MPTP to establish chronic PD mouse model. Behavioral assessments including the pole test and rotarod test were conducted to evaluate the effects of TREM2 deficiency on MPTP-induced motor dysfunction. Immunohistochemistry of TREM2 and tyrosine hydroxylase (TH), immunohistochemistry and immunofluorescence Iba1, Western blot of NLRP3 inflammasome and its downstream inflammatory factors IL-1β and IL-18, and the key pyroptosis factors GSDMD and GSDMD-N were performed to explore the effect of TREM2 on NLRP3 inflammasome and neuroinflammation. In an in vitro experiment, lentivirus was used to interfere with the expression of TREM2 in BV2 microglia, and then lipopolysaccharide (LPS) and adenopterin nucleoside triphosphate (ATP) were used to stimulate inflammation to construct a cellular inflammation model. The expression differences of NLRP3 inflammasome and its components were detected by qPCR and Western blot. In vivo, TREM2 knockdown aggravated the loss of dopaminergic neuron and the decline of motor function. After TREM2 knockdown, the number of activated microglia was significantly increased, and the expression of cleaved caspase-1, NLRP3 inflammasome, IL-1β, GSDMD, and GSDMD-N was increased. In vitro, TREM2 knockdown aggravated the inflammatory response of BV2 cells stimulated by LPS and promoted the activation of NLRP3 inflammasome through the NF-κB pathway. In addition, TREM2 knockdown also promoted the expression of TLR4/MyD88, an upstream factor of the NF-κB pathway. Our vivo and vitro data showed that TREM2 knockdown promoted NLRP3 inflammasome activation and downstream inflammatory response, promoted pyroptosis, and aggravated dopaminergic neuron loss. TREM2 acts as an anti-inflammatory in PD through the TLR4/MyD88/NF-κB pathway, which extends previous findings and supports the notion that TREM2 ameliorates neuroinflammation in PD.

Nanoplastics and chrysene pollution: Potential new triggers for nonalcoholic fatty liver disease and hepatitis, insights from juvenile Siniperca chuatsi - Tiantian Chen; Hewei Jiang; Yaoji He; Yawei Shen; Zequn Huang; Yifeng Gu; Qun Wei; Jinliang Zhao; Xiaowu Chen (Science of The Total Environment, 2024)

Criticality assessment of minerals associated with China's battery technologies - Yawei Huang; Peng Wang; Yao Wang; Heming Wang; Yue Zhang; Xiaozhu Xu; Chao Wang; Qiang Yue; Tao Du; Wei-Qiang Chen (Journal of Cleaner Production, 2024)

Histopathological, physiological, and multi-omics insights into the hepatotoxicity mechanism of nanopolystyrene and/or diclofenac in Mylopharyngodon piceus - Tiantian Chen; Hewei Jiang; Yaoji He; Yawei Shen; Jiajie Fang; Zequn Huang; Yubang Shen; Xiaowu Chen (Environmental Pollution, 2024)

Experimental research on the venting characteristics of methane and coal dust two-phase system mixture explosions - Xingyan Cao; Rui Huang; Yawei Lu; Zhirong Wang; Longtao Fan; Yangqing Zhou; Jianjun Xu (Fuel, 2023)

An overview of the mechanisms underlying hypoxia tolerance differences in aquatic animals and their inspirations for aquaculture - Yawei Shen; Weiwei You; Xuan Luo; Ying Lu; Miaoqin Huang; Caihuan Ke (Reviews in Fish Biology and Fisheries, 2023)

Development of near-infrared reflectance spectroscopy (NIRS) model and genome-wide association study for glycogen and protein content in Pacific abalone - Junyu Liu; Muzhi Zhou; Ziheng Yin; Dan Huang; Liyan Zhu; Weiguang Zou; Wenchao Yu; Yawei Shen; Zekun Huang; Weiwei You; Caihuan Ke; Xuan Luo (Aquaculture, 2023)

Numerical validation of analytical solutions for tunnels and their applicability evaluation index - Yawei Duan; Jingqi Huang; Mi Zhao; Xu Zhao; Huifang Li; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2023)

Analytical solutions for stresses and displacements of tunnels under static and seismic loading - Yawei Duan; Jingqi Huang; Xu Zhao; Mi Zhao; Huifang Li; Xiuli Du (Computers and Geotechnics, 2023)

Enhanced nitrate removal by alcohol-involved nitrate photolysis-induced advanced reduction process - Yawei Xie; Shiyi Ni; Shiming Wang; Chenda Wu; Keqi Huang; Dehua Ma; Lujun Chen; Rui Liu; Hongyuan Liu (Chemical Engineering Journal, 2023)

Study on the assimilation of the sulphate reaction rates based on WRF-Chem/DART - Congwu Huang; Chaoqun Ma; Tijian Wang; Yawei Qu; Mengmeng Li; Shu Li; Bingliang Zhuang; Min Xie (Science China Earth Sciences, 2023)

Protective effect of chicken egg yolk immunoglobulin (IgY) against Spiroplasma eriocheiris infection in Chinese mitten crab - Ying Guo; Yubo Ma; Hendriansyah Endri; Yanlan Huang; Xinyu Pan; Suyue Qiu; Yawei Cao; Wei Gu; Jie Du; Li Wang; Qingguo Meng (Aquaculture, 2023)

The underlying mechanisms of PM2.5 and O3 synergistic pollution in East China: Photochemical and heterogeneous interactions - Yawei Qu; Tijian Wang; Cheng Yuan; Hao Wu; Libo Gao; Congwu Huang; Yasong Li; Mengmeng Li; Min Xie (Science of The Total Environment, 2023)

Genotype by environment interactions in feed efficiency of Pacific abalone (Haliotis discus hannai) reared at different water temperatures - Wenchao Yu; Yawei Shen; Junyu Liu; Weiguang Zou; Zekun Huang; Miaoqin Huang; Ying Lu; Jinwei Ke; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture, 2023)

Genome-wide association and transcriptome studies reveal the segregation mechanism of mantle markings in three-way cross hybrid abalone - Qizhen Xiao; Shihai Gong; Yawei Shen; Yisha Lu; Xinlian Lai; Wenzhu Peng; Zekun Huang; Zhaofang Han; Hongjing Ji; Yang Gan; Xuan Luo; Weiwei You; et al. (Frontiers in Marine Science, 2022)
Trait separation which often appears in shellfish progeny, has been commercially used in shellfish breeding projects. A three-way cross hybrid abalone was produced with heterosis in growth performance and thermal tolerance, and with segregation in mantle marking. However, the inheritance mechanism of mantle marking is unclear. In this study, mantle marking was demonstrated to be a qualitative trait, following simple Mendelian inheritance, through inheritance pattern analysis of the presence of black markings on the mantle in five families of three-way cross of hybrid abalone. Thermal tolerance of abalone was assessed by the Arrhenius breakpoint temperature (ABT) of cardiac performance and a correlation between mantle marking and thermal tolerance of abalone was verified. A genome-wide association study (GWAS) for mantle marking was conducted using 603,067 high-quality single nucleotide polymorphisms (SNPs) derived from 57 individuals with mantle markings (Y group) and 58 individuals without mantle markings (N group). A total of 493 SNPs that were significantly ( p < 2.32E–07) associated with mantle markings were mainly distributed on chromosome 15. In the potential significantly associated region, 80 genes, including pigmentation-related genes PTPRT , PTPRC , PNCA , and CALM4 were annotated. Transcriptome analysis of the two groups showed that the expression levels of these genes ( PTPRT , DDT-b , ATOX1 , SLC6A3 , and GSTO1 ) were significantly different, and they may play important roles in the formation of mantle markings in the three-way cross hybrid abalone. Overall, our data provide valuable information for deciphering the phenotype differences of mantle marking in three-way cross hybrid abalone and help in the molecular marker-assisted breeding in abalone.

Twin peaks of in-hospital mortality among patients with STEMI across five phases of COVID-19 outbreak in China: a nation-wide study - Jianping Li; Nan Zhang; Ziyi Zhou; Xiao Huang; Weiyi Fang; Hongbing Yan; Jiyan Chen; Weimin Wang; Dingcheng Xiang; Xi Su; Bo Yu; Yan Wang; et al. (Science China Life Sciences, 2022)

The neonatal PROC gene rs1799809 polymorphism modifies the association between prenatal air pollutants exposure and PROC promoter methylation - Zhiyuan Li; Meng Yang; Leizhen Duan; Yongxiang Gong; Hongxia Xia; Francis-Kojo Afrim; Hui Huang; Xiaoxue Liu; Fangfang Yu; Yawei Zhang; Yue Ba; Guoyu Zhou (Environmental Science and Pollution Research, 2022)

Preconception ambient temperature and preterm birth: a time-series study in rural Henan, China - Guoyu Zhou; Meng Yang; Jian Chai; Renjie Sun; Junxi Zhang; Hui Huang; Yawei Zhang; Qihong Deng; Lifang Jiang; Yue Ba (Environmental Science and Pollution Research, 2021)

Bioaugmentation-assisted phytoremediation of manganese and cadmium co-contaminated soil by Polygonaceae plants (Polygonum hydropiper L. and Polygonum lapathifolium L.) and Enterobacter sp. FM-1 - Yi Li; Jiamin Lin; Yuanyuan Huang; Yawei Yao; Xueru Wang; Chengzhao Liu; Ying Liang; Kehui Liu; Fangming Yu (Plant and Soil, 2020)

Losartan suppresses the inflammatory response in collagen-induced arthritis by inhibiting the MAPK and NF-κB pathways in B and T cells - Xinming Wang; Xiaoyun Chen; Wei Huang; Pengying Zhang; Yawei Guo; Heinrich Körner; Huaxun Wu; Wei Wei (Inflammopharmacology, 2019)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

LC–MS/MS-Based Metabolome Analysis of Biochemical Pathways Altered by Food Limitation in Larvae of Ivory Shell, Babylonia areolata - Jingqiang Fu; Minghui Shen; Yawei Shen; Wengang Lü; Miaoqin Huang; Xuan Luo; Jinjin Yu; Caihuan Ke; Weiwei You (Marine Biotechnology, 2018)

SNP detection by parallel targeted sequencing from degraded DNA samples in Haliotis diversicolor - Peng Ren; Yawei Shen; Zekun Huang; Miaoqin Huang; Xuan Luo; Jin-Chywan Gwo; Caihuan Ke; Weiwei You (Conservation Genetics Resources, 2017)

Metals compositions of indoor PM2.5, health risk assessment, and birth outcomes in Lanzhou, China - Yaqun Zhang; Suzhen Cao; Xiaoying Xu; Jie Qiu; Mingxia Chen; Dennis Wang; Donghong Guan; Chengyuan Wang; Xiao Wang; Bowen Dong; Huang Huang; Nan Zhao; et al. (Environmental Monitoring and Assessment, 2016)

A Novel Method for Automatic Identification of Motion Artifact Beats in ECG Recordings - Yuewen Tu; Xiuquan Fu; Dingli Li; Chao Huang; Yawei Tang; Shuming Ye; Hang Chen (Annals of Biomedical Engineering, 2012)

Calcineurin Plays an Important Role in the Shell Formation of Pearl Oyster (Pinctada fucata) - Changzhong Li; Yilin Hu; Jian Liang; Yawei Kong; Jing Huang; Qiaoli Feng; Shuo Li; Guiyou Zhang; Liping Xie; Rongqing Zhang (Marine Biotechnology, 2010)